Calix[4]arene‐Based Sensitizers for Host‐Guest Supramolecular Dyads for Solar Energy Conversion in Photoelectrochemical Cells. Issue 34 (7th September 2022) - Decavoli, Cristina; Boldrini, Chiara L.; Faroldi, Federica; Baldini, Laura; Sansone, Francesco; Ranaudo, Anna; Greco, Claudio; Cosentino, Ugo; Moro, Giorgio; Manfredi, Norberto; Abbotto, Alessandro
Abstract: The photogeneration of electricity and solar fuels by solar irradiation in photoelectrochemical cells is one of the sectors with the highest growth potential in the decarbonised society. However, the use of different components, in particular photosensitizers and catalysts, can present problems of charge transfer efficiency at the interface, leading to lower final efficiencies. In this work we present novel integrated photosensitizer‐catalyst dyads based on robust and, at the same time, flexible host‐guest non‐covalent interactions through the use of calix[4]arene cavities. Current photogeneration in photoelectrochemical cells showed twice greater efficiency in the integrated calixarene‐based host‐guest dyads compared to the traditional architecture based on the separate photosensitizer‐catalyst pair. Molecular dynamics studies have shown that the enhanced performance originates from an optimization of the distances between the centres of the photosensitizer, catalyst and semiconductor involved in the charge transfer processes, thus allowing a higher final efficiency of the charge photogeneration process. Abstract : A calix[4]arene moiety has been incorporated in the structure of a di‐branched D‐(π‐A)2 metal‐free organic sensitizer to exploit host‐guest interaction with a proper Ru(II) water oxidation catalyst, so to enhance water oxidation in a photoactive device. This provides a new supramolecular strategy for constructing photocatalytically active electrodes for water splitting.